Realizacja przekształceń własnościowych i strukturalnych w rolnictwie Dolnego Śląska (stan na 31.12.2005) - Tańska-Hus, Bożena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
Local departament of the APA in Wrocław realizing transformations by the end of December 2005 took over in general 482562 ha. Most of intent properties were mainly leased. About 71% ares of grounds became rented in complexes about surface 100 ha, greater, and 29% in plots to 100 ha. There are no legal acts in range of lease causes, that part of grounds "comes back" from leases, how-ever lease and purchase of grounds influenced in considerable degree the increase and creation of new farming farms on grounds of Lower Silesia and in consequence influenced improvement of agrarian structure in this area. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 210-215